Trapping of Whistler Waves in the Magnetic Hole at a Dipolarization Front - K. Jiang; S. Y. Huang; X. D. Yu; Z. G. Yuan; Q. Y. Xiong; R. T. Lin; L. Yu (Geophysical Research Letters)
Abstract Dipolarization fronts (DFs) host plentiful dynamics in the magnetotail. Small‐scale magnetic structures and waves are frequently found at and around the DFs. Whistler waves are closely related to DFs, and the flux pileup regions (FPRs) behind DFs are thought to be the source regions of the whistler waves around DFs. Statistically, whistler waves are much more frequently observed in FPRs than at DFs. Here, we present an observation of whistler waves in a magnetic hole at a DF. Theoretical calculations show that the observed whistler waves can be trapped in the magnetic hole. Furthermore, theoretical calculations suggest that whistler waves cannot be trapped at a DF if the DF has no sub‐structures. Our results indicate the importance of the magnetic structures on the propagation of whistler waves around the DFs and could explain why whistler waves are rarely observed at the DFs.